Property valuation - Wyatt, Peter, 1968- (Wiley, 2023)
"Real estate is an essential part of life, providing the buildings for living, working, learning and leisure activities. Non-domestic real estate is comprised of a huge range of buildings, including office, retail, industrial, leisure, medical and hotel properties. In the UK, the commercial real estate sector has a market value of around £1.7 trillion (2019 data) and is one of the fundamental building blocks of the UK economy, directly employing more than one million people and supporting an additional million, while also contributing over £100 billion to the UK's economy each year (about 7% of UK GVA). Worldwide, it is estimated that the value of commercial real estate is around $33.3 trillion, with the US ($8.1t), China ($3.6t), Japan ($2.8t), Germany ($1.7t) and the UK ($1.7t) being the largest markets (2017 data). China also accounts for the largest share of global residential value, thanks to national house price growth and a rapid programme of housebuilding. Emerging markets, especially in Asia, are also experiencing fast growth in both commercial and residential property value"--